x + x +x =12 - 11 +35 =
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
3 x 8 x 76 + 2 x 35 x 12 - 4 x 11 x 6
= ( 3 + 2 ) x ( 8 + 35 ) x ( 76 + 12 ) - 4 x 11 x 6
= 5 x 43 x 88 - 4x 11 x 6
= ( 5-4 ) x ( 43 - 11 ) x ( 88 - 6 )
= 1 x 32 x 82
= 2624
![](https://rs.olm.vn/images/avt/0.png?1311)
x - ( 17 - x ) = x + 3
<=> 2x - 17 = x + 3
<=> x = 20
Vậy x = 20
- ( x + 12 ) + 35 = - 47
<=> - x - 12 = - 47 -35
<=> x = 47 + 35 - 12
<=> x = 60
Vậy x = 60
15 - ( x + 32 ) = - 11
<=> 15 - x - 32 = - 11
<=> - x - 17 = - 11
<=> - x = - 11 + 17 = 6
<=> x = - 6
Vậy x = - 6
K chắc lắm
a)\(x-\left(17-x\right)=x+3\)
\(\Leftrightarrow x-17+x=x+3\)
\(\Leftrightarrow x+x-x=17+3\)
\(\Leftrightarrow x=20\)
b)\(-\left(x+12\right)+35=-47\)
\(\Leftrightarrow-x-12+35=-47\)
\(\Leftrightarrow-x=-47+12-35\)
\(\Leftrightarrow-x=-70\)
\(\Leftrightarrow x=70\)
c)\(15-\left(x+32\right)=-11\)
\(\Leftrightarrow15-x-32=-11\)
\(\Leftrightarrow-x=-11-15+32\)
\(\Leftrightarrow-x=6\)
\(\Leftrightarrow x=-6\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\dfrac{x}{12}=\dfrac{6}{9}\)
\(\Rightarrow x=\dfrac{12\cdot6}{9}=8\)
b) \(\dfrac{9}{15}=x+\dfrac{11}{35}\)
\(\Rightarrow x=\dfrac{9}{15}-\dfrac{11}{35}\)
\(\Rightarrow x=\dfrac{2}{7}\)
c) \(x+\dfrac{6}{5}=\dfrac{x}{2}\)
\(\Rightarrow2\left(x+\dfrac{6}{5}\right)=x\)
\(\Rightarrow2x+\dfrac{12}{5}=x\)
\(\Rightarrow2x-x=-\dfrac{12}{5}\)
\(\Rightarrow x=-\dfrac{12}{5}\)
\(a,\dfrac{x}{12}=\dfrac{6}{9}\\ \Leftrightarrow x=12\cdot\dfrac{6}{9}\\ \Leftrightarrow x=8\\ b,\dfrac{9}{15}=x+\dfrac{11}{35}\\ \Leftrightarrow x=\dfrac{9}{15}-\dfrac{11}{35}\\ \Leftrightarrow x=\dfrac{2}{7}\\ c,x+\dfrac{6}{5}=\dfrac{x}{2}\\ \Leftrightarrow\dfrac{x}{2}=-\dfrac{6}{5}\\ \Leftrightarrow x=-\dfrac{12}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ x - ( 17 - x ) = x + 3
=> x - 17 + x = x + 3
=> 2. x - 17 = x + 3
=> 2. x - x = 3 + 17
=> x = 20
b/ - ( x + 12 ) + 35 = - 47
=> -x - 12 + 35 = -47
=> -x + 23 = -47
=> -x = -47 - 23 = -70
=> x = 70
c/ 15 - ( x + 32 ) = - 11
=> x + 32 = 15 - (-11) = 15 + 11 = 26
=> x = 26 - 32 = -6
![](https://rs.olm.vn/images/avt/0.png?1311)
\(46\cdot99\)
\(=46\cdot\left(100-1\right)\)
\(=46\cdot100-46\)
\(=4600-46\)
\(=4554\)
___________
\(34\cdot11\)
\(=34\cdot\left(10+1\right)\)
\(=34\cdot10+34\)
\(=340+34\)
\(=374\)
___________
\(25\cdot12\)
\(=5\cdot5\cdot12\)
\(=5\cdot60\)
\(=300\)
__________
\(15\cdot4\)
\(=15\cdot2\cdot2\)
\(=30\cdot2\)
\(=60\)
____________
\(45\cdot6\)
\(=45\cdot2\cdot3\)
\(=90\cdot3\)
\(=2700\)
________
\(13\cdot99\)
\(=13\cdot\left(100-1\right)\)
\(=13\cdot100-13\)
\(=1300-13\)
\(=1287\)
______________
\(16\cdot19\)
\(=16\cdot\left(20-1\right)\)
\(=16\cdot20-16\)
\(=320-16\)
\(=304\)
_____________
\(35\cdot98\)
\(=35\cdot\left(100-2\right)\)
\(=35\cdot100-35\cdot2\)
\(=3500-70\)
\(=3430\)
____________
\(125\cdot16\)
\(=125\cdot8\cdot2\)
\(=1000\cdot2\)
\(=2000\)
___________
\(47\cdot101\)
\(=47\cdot\left(100+1\right)\)
\(=47\cdot100+47\)
\(=4700+47\)
\(=4747\)
46 x 99 =4554 , 34 x 11 = 374 , 25 x 12 =- 300 , 15 x 4 = 60 , 45 x 6 = 270 , 13 x 99 = 1287 , 16 x 19 = 304
35 x 98 = 3430 , 125 x 16 = 2000 , 47 x 101 = 4747
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{x+32}{11}+\frac{x+33}{12}=\frac{x+34}{13}+\frac{x+35}{14}\)
\(\Leftrightarrow\left(\frac{x+32}{11}-1\right)+\left(\frac{x+33}{12}-1\right)=\left(\frac{x+34}{13}-1\right)+\left(\frac{x+35}{14}-1\right)\)
\(\Leftrightarrow\frac{x-21}{11}+\frac{x-21}{12}=\frac{x-21}{13}+\frac{x-21}{14}\)
\(\Leftrightarrow\left(x-21\right)\left(\frac{1}{11}+\frac{1}{12}-\frac{1}{13}-\frac{1}{14}\right)=0\)
Vì \(\left(\frac{1}{11}+\frac{1}{12}-\frac{1}{13}-\frac{1}{14}\right)\ne0\)
\(\Rightarrow x-21=0\Rightarrow x=21\)
\(\frac{x+32}{11}+\frac{x+33}{12}=\frac{x+34}{13}+\frac{x+35}{14}\)
\(\Leftrightarrow\left(\frac{x+32}{11}-1\right)+\left(\frac{x+33}{12}-1\right)=\left(\frac{x+34}{13}-1\right)+\left(\frac{x+35}{14}-1\right)\)( trừ cả hai vế cho 2 )
\(\Leftrightarrow\frac{x-21}{11}+\frac{x-21}{12}=\frac{x-21}{13}+\frac{x-21}{14}\)
\(\Leftrightarrow\frac{x-21}{11}+\frac{x-21}{12}-\frac{x-21}{13}-\frac{x-21}{14}=0\)
\(\Leftrightarrow\left(x-21\right)\left(\frac{1}{11}+\frac{1}{12}-\frac{1}{13}-\frac{1}{14}\right)=0\)
Mà \(\frac{1}{11}+\frac{1}{12}-\frac{1}{13}-\frac{1}{14}\ne0\)
\(\Rightarrow x-21=0\)
\(\Leftrightarrow x=21\)
Vậy \(x=21\)
x + x + x = 12 - 11 + 35
x + x + x = 36
x = 36 : 3
x = 12
Vậy x = 12
Học tốt!!!
x + x + x = 12 - 11 + 35
3x = 1 + 35
3x = 36
x = 36 : 3
x = 12